Making sense of Starbucks' anti-bias training and the arrests of two African American men: A thematic analysis of Whites' Facebook and Twitter comments. (December 2019) - Karlsen, Annika S.; Scott, Katie D.
Highlights: Racial profiling and discrimination frequently occur in consumer settings. To address discrimination, Starbucks' facilitated nationwide anti-bias trainings. White social media users expressed fractured opinions regarding the training. Color-blind and color conscious frames were used to support and oppose efforts. Anger, annoyance, and even appreciation were expressed towards the training.